CONSTRUCTION NETWORK REFORMS AND THEIR DEVELOPMENT TENDENCIES (Marketing Journal, 2025)
This article provides a comprehensive analysis of institutional reforms implemented in the construction sector of the Republic of Uzbekistan, their socio - economic effectiveness, and development trends. The study examines state programs and regulatory acts adopted during 2020 –2025, as well as the processes of digital governance, implementation of innovative and green construction technologies.
Keywords: construction sector; institutional reforms; management efficiency; investments; sustainable development; digital governance; green construction; economic growth